MENGELOLA OBJEK VITAL, PENGAMANAN FILE, DAN PENGAMANAN CYBER TERHADAP MANAJEMEN SEKURITI PADA PT. PERTAMINA (PERSERO) - Edy Soesanto; Anna Wijayanti; Muhamad Elzan Musyafa; Nurul Cahyani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
Pertamina (Persero) is the only BUMN (State Owned Enterprise) engaged in the integrated oil and gas business, starting from the upstream to downstream scope of work with assets that really need to be maintained. PT Pertamina (Persero) ensures that meeting the needs for fuel and LPG as well as providing services to the community remain the Company's main priorities. As a BUMN, Pertamina, including all workers, is responsible for carrying out the Government's mandate to ensure national energy security. The purpose of this study is to determine vital objects, file security, and cyber security against security management at PT. Pertamina (Persero). This research method uses qualitative research with a Systematic Review approach, the source of data used in this study is secondary data, namely data obtained or collected by researchers from various existing sources. Secondary data can be in the form of data from the Annual Report of PT. Pertamina (Persero) and so on. The results of research in this journal serve as additional information material and input for companies that can be taken into consideration in managing Vital Objects, File Security and Cyber ​​​​Security for Security Management at PT. Pertamina (Persero), as with construction projects, the risk of work accidents disrupts the activities of the project workers.